Nursing Practice Experience for Stroke Patients of Nursing Students among Cultural Diversity at the Stroke Unit in Naradhiwasrajanagarindra Hospital, Narathiwat, Thailand - Chansintop, Sawinee; Dereh, Nurdeenee; Kongkakul, Usanee; Butmata, Vararat (Princess of Naradhiwas University Journal, 2021)
The aim of this phenomenological study was to determine nursing experience in taking care of stroke patients among cultural diversity in nursing students at the stroke unit in Naradhiwasrajanagarindra Hospital, Narathiwat, Thailand. The purposive sampling was employed to recruit 10 participants following the inclusion criteria: 1) the third years nursing students of faculty of nursing, Princess of Naradhiwas University; and 2) practicing in adult and elderly care II subject at the stroke unit in Naradhiwasrajanagarindra Hospital at least 2 weeks. The data were collected by using individual in-depth interview from October to December, 2020. The data were analyzed by applying Colaizzi’s approach. Trustworthiness of qualitative study was established by following Lincoln and Guba’s criteria. The results showed that there were two aspects of nursing experiences while practicing in the cultural diversity circumstances. First, the nursing experiences is the distinction of patient’s way of life, beliefs, languages, traditions and culture, family, and community needed to be mainly concerned. Second, there were three main nursing activities employed in the cultural diversity which consisted of 1) the evaluation of the patients religion’s concerns, 2) allowing the patients to practice their own religion activities, and 3) providing nursing cares regarding the patients’ cultural diversity without contradict to physician’s plan of treatment. The findings of this study provides understanding of nursing experiences while practicing with the patients who have stroke in the cultural diversity circumstances, and can be used to develop nursing teaching and nursing skills among cultural diversity.